Efeitos do treinamento muscular inspiratório de alta intensidade na espessura diafragmática em pacientes pós-revascularização do miocárdio: ensaio clínico randomizado - Silva, André Felipe Santos da (2019)
Moderate to high intensity inspiratory muscle training (IMT) has shown the presence of a clinical picture (CR) in patients undergoing coronary artery bypass grafting (CABG). Currently, the inclusion of IMT in Phase II has gained strength, since the repercussions on lung function and the reduction of functional capacity are still present late.Ultrasonography has been shown to be useful in assessing the anatomical characteristics of many muscle groups and considered as an alternative proposal for function analysis and diaphragmatic thickness.The present study aimed to evaluate the impact of the addition of moderate to high intensity TMI associated with short-term aerobic and resistive exercise on diaphragmatic thickness in post-CABG patients in Phase II of CR. This was a randomized double-blind clinical trial involving 19 post-CABD patients randomly divided into intervention group (GI; n = 10) submitted to moderate to high intensity IMT associated with aerobic and resistance exercise, with progression of TMI and sham group (GS; n = 9) who performed IMT combined with aerobic and resistance exercise, whose IMT load was minimal and maintained constant for 12 weeks, twice weekly, 5 sets of 10 repetitions. Pre-and post-intervention were evaluated: initial evaluation (anamnesis), diaphragmatic thickness (ultrasonography), quality of life (MacNew QLMI), respiratory muscle strength (manovacuometry), functional capacity (distance walked in the 6-minute walk test - DPTC6M) , respiratory muscle resistance (incremental test and constant test) and palmar grip strength (FPP). In the statistical analysis, the normality of the variables was evaluated by the Shapiro-Wilk test. Continuous variables were presented in mean ± standard deviation (SD) and 95% confidence interval (95% CI), as well as categorical variables in absolute frequencies and percentages. The intragroup comparison was performed using Student's T-test. The comparison between groups was performed using two-way ANOVA. The size of the effect was determined from Cohen's d. The level of significance was 5% (p <0.05). There was a significant 13% increase in diaphragmatic muscle thickness in IG (0.02cm 95% CI 0.001 to 0.036, Cohen d 0.66). In relation to MIP, there was a significant increase of 31% in IG (26.60cmH2O 95% CI 16.37 to 36.8; Cohen d 0.38). The variable inspiratory muscle resistance showed a significant of 29% increase in the PimáxS in the GI (16.1cmH2O 95% CI 0.46 to 31.74, Cohen d 0.85). DPTC6M and PEmax showed a significant increase in both GI and GS, with no significant difference in comparison between groups. In the comparison between groups, no significant differences were observed for all evaluated outcomes. The results found in this study suggest that MRI of moderate to high intensity in the short term improved diaphragmatic thickness, maximal inspiratory pressure and sustained maximum inspiratory pressure in post- CABG patients.